PHARMACEUTICAL PREPARATION OF HEMGARBHA POTTALI - Rathod Hetal; Gupta Priyanka; Lekshmipriya; M R Pandya (International Journal of Applied Ayurved Research, 2018)
Rasa sastra is one of the important branch of Ayurveda which deals with mineral and herbomineral pharmaceutical preparations like kharliya rasayana, parpati rasayana, kupipakva rasayana and pottali rasayana. Pottali rasayana is one among rasa aushadhi which is very effective and also known as emergency medicine. Pottali rasayana prepared by different method. Here we prepare with gandhak drava swedana method. The process of pottali kalpana is very unique, and from other dosage forms it has qualities like small dose, very high potency, easy to handle, and maximum shelf life. In Hemagarbha pottali rasa main drugs are suddha parad, suddha gandhak, tamra bhasma and swarna bhasma which gives compact form by bhavna with kumari swarwsa. In this article we attempted to described different methods of preparation and regarding pharmaceutical process of Hemagarbha pottali rasa in detail.